First Report of Gametogenesis and Spawning for the Invasive Alga Caulerpa cylindracea in the Tyrrhenian Sea: The Key Role of Water Motion and Temperature - Caronni, Sarah; Delaria, Maria Anna; Gentili, Rodolfo; Montagnani, Chiara; Navone, Augusto; Panzalis, Pieraugusto; Citterio, Sandra (Frontiers in Marine Science, 2021)
In this study, gamete release by Caulerpa cylindracea was investigated for the first time in the Tyrrhenian Sea (Sardinia, Western Mediterranean), focusing on the main environmental factors triggering gametogenesis and spawning of the species. For this purpose, a combination of field and laboratory experiments was conducted. First, a 2-year mensurative experiment was performed in the field during summer to individuate and quantify the occurrence of C. cylindracea gametogenesis and spawning events, linking them to environmental conditions. Then, based on the results of the field work, a laboratory experiment was performed to directly test, under controlled conditions, the effect on the above-mentioned processes of two abiotic factors that appeared to play a key role in species gamete release processes in the area: sea water temperature and water movement. During the 2 years of field research, several gametogenesis events were recorded in the study area and two spawning events also occurred. Significant differences were observed between the ratio of fertile and total thalli and between releasing thalli (RT) and fertile thalli (FT), among sites with different hydrodynamic conditions and sampling periods with different sea water temperatures. Overall, these results suggest that C. cylindracea sexual reproduction also occurs in the Tyrrhenian Sea, and that, therefore, new genotypes that favor the invasive profile of the species could be produced in the basin, where both its gametogenesis and spawning seem to be mainly regulated by water movement and sea water temperature.